2020
DOI: 10.7150/thno.49422
|View full text |Cite
|
Sign up to set email alerts
|

First clinical study of a pegylated diabody 124I-labeled PEG-AVP0458 in patients with tumor-associated glycoprotein 72 positive cancers

Abstract: Through protein engineering and a novel pegylation strategy, a diabody specific to tumor-associated glycoprotein 72 (TAG-72) (PEG-AVP0458) has been created to optimize pharmacokinetics and bioavailability to tumor. We report the preclinical and clinical translation of PEG-AVP0458 to a first-in-human clinical trial of a diabody. Methods: Clinical translation followed characterization of PEG-AVP0458 drug product and preclinical biodistribution and imaging assessments of Iodine-124 trace l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…19−21 Scott et al used 124 I-PEG-AVP0458 (a pegylated diabody) for detecting tumorassociated glycoprotein in 72 positive cancer samples. 19 Wang et al demonstrated that 124 I-toripalimab was a safe tracer for PET with acceptable dosimetry. 20 Guo et al reported that 124 Itrastuzumab was feasible for the detection of HER2-positive lesions in primary and metastatic gastric cancer and to quantitatively differentiate HER2-positive and HER2-negative lesions.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19−21 Scott et al used 124 I-PEG-AVP0458 (a pegylated diabody) for detecting tumorassociated glycoprotein in 72 positive cancer samples. 19 Wang et al demonstrated that 124 I-toripalimab was a safe tracer for PET with acceptable dosimetry. 20 Guo et al reported that 124 Itrastuzumab was feasible for the detection of HER2-positive lesions in primary and metastatic gastric cancer and to quantitatively differentiate HER2-positive and HER2-negative lesions.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Iodine-124 was selected as a medical positron radionuclide because it has a long half-life ( T 1/2 = 4.2 d) that matches the pharmacokinetics of the antibody in vivo. Furthermore, given its slow metabolism, iodine-124 is beneficial for obtaining images with low-radiation background. , The simplicity of labeling using the Iodogen method also provided an advantage; owing to these advantages, radioimmunoimaging with iodine-124 has been commonly used in clinical trials. Scott et al used 124 I-PEG-AVP0458 (a pegylated diabody) for detecting tumor-associated glycoprotein in 72 positive cancer samples . Wang et al demonstrated that 124 I-toripalimab was a safe tracer for PET with acceptable dosimetry .…”
Section: Discussionmentioning
confidence: 99%
“…Testing our hypothesis could involve repeating our clinical studies using one of the humanized fragments of the mMoAb CC49 developed in the last decade ( 14 , 146 – 148 ). There are many radionuclides that can be used instead of 125 I, but it is critical to match the antibody’s clearance to that of the radionuclide.…”
Section: Discussionmentioning
confidence: 99%
“…To improve tumour penetration, several strategies have been adopted and integrated, including construction of smaller antibody derivatives such as scFv or diabodies and reducing renal clearance with incorporation of PEG. Further improvement of targeting antibodies and derivatives has been demonstrated for the pegylated diabody (Avibody) PEG-AVP0458, that targets the tumour-associated glycoprotein TAG-72 of ovarian and prostate cancers [ 46 ]. High tumour/blood ratios, a favourable bio-distribution (high tumour penetration with minimal organ uptake), and prolonged T 1/2 were reported.…”
Section: Further Challenges Of Solid Tumours In Particular Glioblastomamentioning
confidence: 99%